Industrial and intellectual property: Patent protection for medicines and international trade - Romero Matute, Yeray (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
As a consequence of technological progress and the elimination of obstacles to internationaltrade, there has always been a certain concern when adopting regulations to ensure the protectionof industrial and intellectual property rights. It is for this reason that obtaining a patent and the exclusiveright to exploit it entails the need to ensure that this “right” is valid in a given country. From the pointof view of private international law, and given that it is the inherent rights associated with certain intangibleproducts that are to be protected, the determination of a court, as well as the determination of theapplicable law, are crucial aspects when it comes to protecting these rights.
Keywords: Industrial property; patents; medicines; international; private